Retinal Screening of Coats Disease Using Electroretinography - Adhami-Moghadam, Parnian; Shushtarian, Seyed Mohammad Masoud; Adhami-Moghadam, Farahad (Journal of Ophthalmic and Optometric Sciences, 2021)
Background: Coats is a retinal disorder causing dilation of blood vessels in the human retina. The present study aims to measure electroretinography (ERG) in patients suffering from Coats disease. Material and Methods: 11 (20 eyes) male patients suffering from Coats were selected for the present study. Electroretinography was measured in the patient group using the Mangoni machine. The result was compared with the 11 (22 eyes) normal population following the ERG test. SPSS version 22 was used for this purpose. Results: The case and control groups were not significantly different in age, while a significant difference was observed in Best corrected visual acuity. BCVA between the two groups. Furthermore ( 110.9±8.63 and 93.09 ± 8.04 in control and case respectively ) , the difference between the mean amplitude of ERG, b wave was statistically significant as far as patient and normal groups were concerned. Conclusion: Coats disease damages the retina, which can be measured by the amplitude of ERG, b wave.